Flow-Induced Acoustics in Corrugated Pipes (Communications in Computational Physics, 2011)
When gas flows through corrugated pipes, pressure waves interacting withvortex shedding can produce distinct tonal noise and structural vibration. Based onestablished observations, a model is proposed which couples an acoustic pipe and self-excitedoscillations with vortex shedding over the corrugation cavities. In the model,the acoustic response of the corrugated pipe is simulated by connecting the losslessmedium moving with a constant velocity with a source based on a discrete distributionof van der Pol oscillators arranged along the pipe. Our time accurate solutions exhibitdynamic behavior consistent with that experimentally observed, including the lock-infrequency of vortex shedding, standing waves and the onset fluid velocity capable ofgenerating the lock-in.